JAJAN PASAR SEBAGAI MEDIA STIMULASI ASPEK PERKEMBANGAN ANAK USIA DINI DALAM PEMBELAJARAN BILINGUAL SEBAGAI SALAH SATU METODE MEMPERTAHANKAN KEARIFAN LOKAL - Ririn Ambarini; Subur Laksmomo W; Dian Ayu Z (Universitas PGRI Semarang, 2015)
This research is a model research of traditional snack as simulation media of child?óÔé¼Ôäós development in bilingual learning as method to maintain local wisdom. The model of traditional snack as simulation media of child?óÔé¼Ôäós development in bilingual learning as method to maintain local wisdom start with needs analysis then develop and construct the learning model. The learning model is expected to be used by kinder garden teacher as reference to increase student?óÔé¼Ôäós communication ability in bilingual learning through traditional snack as simulation media of child?óÔé¼Ôäós development. This research continued with prior study by literacy analysis and construct learning draft model then made research instruments. The last step of this research was wrote learning model of traditional snack as simulation media of child?óÔé¼Ôäós development in bilingual learning as method to maintain local wisdom. The result of this research show t-table 0.05 value was 2.042 beside the t-test result was 3.61. t-test result was higher than t-table, it mean that the research hypothesis was accepted and student?óÔé¼Ôäós communication has significantly result after learning model of traditional snack as simulation media of child?óÔé¼Ôäós development was applied in learning process. Keywords: traditional snack, simulation media, the development of children, bilingual learning, local wisdom